ANALISIS UPAYA MENINGKATKAN KEMAMPUAN MEMBACA ANAK USIA 7 TAHUN MELALUI BIMBINGAN BELAJAR DI CALISTUNG ISLAM BATAM - harahap, ito (Hamka Ilmu Pendidikan Islam, 2025)
This study aims to determine the methods and strategies of the Islamic Calistung Learning House in Batam in improving reading skills in seven-year-old children. to determine the level of success of the method. The method used in this study is a qualitative method with a descriptive research type. Information taken from the author is a teacher at the Islamic Calistung tutoring center in Batam. Data was taken from the results of observations and interviews at the Islamic Calistung learning house in Batam, after which it was analyzed according to experts from previous researchers. Initially, children had difficulty distinguishing similar letters and had difficulty combining letters that had double consonants, based on the results of the study, it showed that children who underwent guidance at the Islamic Calistung learning house had good changes and improvements in their reading abilities.